Career choices and determining factors among final year medical students in Lagos Nigeria - Bode Falase; Setemi Olufemi; Ayowade Funmilayo Adeleye; Adeola O Amogbonjaye; Samiat Sunmola; Ayomide Olaiya; Omowumi Folaranmi (Nigerian Journal of Medicine, 2022)
Background: Identifying the factors that influence the choices medical students make regarding their careers can prove invaluable in the management of healthcare manpower. Aim: The aim of this study was to determine the career choices and the determining factors for these choices among final year medical students at the Lagos State University College of Medicine, Nigeria. Materials and Methods: This study is a cross-sectional survey of two consecutive final year classes with a total of 141 students surveyed in February 2014 and February 2015. Results: A total of 141 students were surveyed. 75.2% intended to specialise, the most common specialties being: Surgery (29.2%), Paediatrics (14.2%), Obstetrics and Gynaecology (13.2%) and Internal medicine (13.2%). More men preferred surgery (43.5% vs 18.3%; p = 0.005) and more women paediatrics (20% vs 6.5%; p = 0.011). 24.8% did not want to specialise. The reasons included: rigours of residency (48.6%), unacceptable hours of practice (34.3%), difficulty getting placements (28.6%) and family requirements (22.9%). 48.1% of the respondents chose to do their residency abroad, 27.4% chose to stay at home and 24.5% were undecided. The main factors influencing choice of residency abroad were better exposure (88.2%), improved standards of living (82.4%), avoiding incessant strike actions (80.4%) and better financial rewards (72.5%). Conclusion: Most students showed a preference for the core clinical specialties with significant gender disparity in specialty preference. The potential for continuous 'brain drain' is also identified. Appropriate steps should be taken to mitigate the factors identified that influenced these choices, to protect the future medical workforce.